PENGARUH FINANCIAL DISTRESS, FIRM RISK DAN CAPITAL INTENSITY TERHADAP TAX AGGRESSIVENES (Studi Empiris Pada Perusaahaan Manufaktur Non Cyclical Yang Terdaftar Di BEI Tahun 2019-2023) - Zulfan Izulsalam; Nisak Ruwah Ibnatur Husnul (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of financial distress, firm risk and capital intensity on tax aggressiveness in companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The population in the study were 14 manufacturing companies in the Cylica sub-sector and components registered in the 2019-2023 period. This research is quantitative research using secondary data by collecting it via www.idx.co.id to get the information needed about the company. The amount of data required is 70, consisting of the 2019-2023 period and 14 companies. The sampling process uses purposive sampling. The researcher tested the F statistic with the aim of finding out whether there was a significant joint influence between the independent variables and was able to predict tax aggressiveness statistically. Hypothesis testing with the t test basically shows how much influence an individual independent variable has in explaining the dependent variable. The data analysis technique used is multiple linear regression analysis using the E-views version 10 program as a data analysis tool. The population in this research is all manufacturing companies in various industries from 2018 to 2019. 2023 which are listed on the Indonesian Stock Exchange (BEI). The results of this research partially show that financial difficulties, company risk and capital intensity have no effect on tax aggression. Meanwhile, the research results simultaneously show that Financial Distress, Firm Risk and Capital Intensity influence Tax Aggressiveness